Probing electrical tuning of hair cells with a Zap current method in the intact amphibian papilla of bullfrogs. Issue 2 (2nd November 2016) - Frolov, Daniil; Li, Geng‐Lin
Abstract: Most, if not all, modern vertebrate species have evolved exquisite inner ears to discriminate acoustic signals of different frequencies, through a process called frequency tuning. For non‐mammalian species, at least part of frequency tuning has been attributed to intrinsic electrical properties of hair cells, i.e. electrical tuning. Since it was first discovered, the traditional method to assess electrical tuning has been to inject step current into hair cells and examine dampened membrane voltage oscillation. However, this method is not applicable for hair cells that do not oscillate. In this study, we developed a Zap current method that can be unbiasedly applied to all hair cells regardless of their oscillating behavior. Similar to a chirp sound in acoustic stimulation, a Zap current is a sinusoidal current with the frequency increased linearly with time. We first validated this new method with the traditional step current method on hair cells with dampened membrane voltage oscillation, and then applied it to all hair cells in the intact amphibian papilla of bullfrogs. We found that while hair cells with dampened membrane voltage oscillation are sharply tuned, non‐oscillating hair cells are broadly tuned. In addition, we found a third type of hair cells, which oscillate continuously and are extremely sharply tuned, with multiple peaks that are reminiscent of harmonics in the mammalian cochlea. In conclusion, the new Zap current method provides an unbiased way to assess electrical tuning, and it reveals an underappreciated heterogeneity of electrical tuning in the bullfrog amphibian papilla. Abstract : The authors developed and validated a new Zap current method to measure electrical tuning of hair cells. When applied to the bullfrog amphibian papilla, the new method revealed a greater heterogeneity of electrical tuning that the traditional step current method failed to uncover.